2008
DOI: 10.1055/s-2008-1043162
|View full text |Cite
|
Sign up to set email alerts
|

Prävalenz der Hyperhomocysteinämie bei der Thrombangiitis obliterans: Spielt Homocystein pathogenetisch eine Rolle?

Abstract: Hyperhomocysteinaemia occurs frequently in patients with TAO. It may play an important and nicotine-independent role in its pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…In our study, the plasma level of homocysteine was significantly higher in patients with Buerger’s disease as compared to atherosclerosis and healthy cases before treatment. (p < 0.001) The higher values of plasma homocysteine levels in Buerger’s disease patients and simultaneously the higher prevalence of tobacco usage in this group (90.9% of cases) and also higher plasma levels of homocysteine in smoker cases of 3 groups was compared to the initial measurement in all patients, suggests that tobacco could be the principle cause of hyperhomocysteinemia in such patients, which also has been revealed in other studies (4, 6, 12, 14). The effect of folic acid therapy on elevated homocysteine levels in some medical conditions has been evaluated in a variety of studies.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In our study, the plasma level of homocysteine was significantly higher in patients with Buerger’s disease as compared to atherosclerosis and healthy cases before treatment. (p < 0.001) The higher values of plasma homocysteine levels in Buerger’s disease patients and simultaneously the higher prevalence of tobacco usage in this group (90.9% of cases) and also higher plasma levels of homocysteine in smoker cases of 3 groups was compared to the initial measurement in all patients, suggests that tobacco could be the principle cause of hyperhomocysteinemia in such patients, which also has been revealed in other studies (4, 6, 12, 14). The effect of folic acid therapy on elevated homocysteine levels in some medical conditions has been evaluated in a variety of studies.…”
Section: Discussionsupporting
confidence: 77%
“…Buerger’s disease or Thromboangiitis obliterans (TAO) is a peripheral vascular disease with a questionable pathophysiology, natural course, and definitive treatment. Stammler (12) and Bergmark (13) have shown that the presence of high plasma levels of homocysteine in Buerger’s disease patients. So, hyperhomocysteinemia may play a meaningful role in the pathophysiology of Buerger’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…In the past years, several association between Buerger's disease and alteration of haemostasis have been suggested [5]. In these reports a role of hyperhomocysteinemia playing a pathogenetic role in Buerger's disease was ruled out, but univocal data are lacking since the majority of reports were based on single case observations or small populations [5,11,12]. On the other hand, reports on the role of MTHFR C677T gene variant, a cause of hyperhomocysteinemia, as a trigger factor of Buerger's disease did not confirm this association [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown a possible relationship between TAO and hypercoagulable states, although the details of such relation are still unknown. There are cases associated with deficiencies in protein S and protein C [7], antiphospholipid antibodies [8] and hyperhomocysteinemia [9]. A study has demonstrated that high concentrations of anticardiolipin antibodies are correlated with an earlier and more severe form of the condition, including higher amputation rates [10].…”
Section: Introductionmentioning
confidence: 99%